Pengaruh Citra Merek, Kualitas Produk dan Harga Terhadap Keputusan Pembelian Iphone (Studi Kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Bandar Lampung) - Selfia Alkemega; M. Fikri Ramadhan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Although the iPhone brand is not among the best-selling smartphones in Indonesia, iPhone sales are still the highest in the world. The purpose of this study is to analyze the influence of brand image, product quality, and price on the iPhone purchase decisions of students of Faculty of Economics, Bandar Lampung University. A total of 79 student respondents were used as the sample for this quantitative study. Methods used include multiple regression, coefficient of determination, hypothesis testing (t-test and F-test). The results show that brand image and product quality have a positive impact on purchase decisions, while price has a negative impact on iPhone smartphone purchase decisions. The F-test results show that brand image, product quality, and price together have a significant impact on purchasing decisions. These three variables have 58% predictive power in iPhone brand purchasing decisions, with other factors influencing the remaining factors.